2016
DOI: 10.1021/acs.macromol.5b01249
|View full text |Cite
|
Sign up to set email alerts
|

Blue-Greenish Electroluminescent Poly(p-phenylenevinylene) Developed for Organic Light-Emitting Diode Applications

Abstract: A novel electroluminescent poly(p-phenylenevinylene) (PPV) derivative was synthesized via the Gilch route, which emits in the blue-greenish region. The required monomer synthesis is a multistep process starting from catechol and does not involve any critical step. The polymer synthesis itself proceeds via standard Gilch conditions and results in constitutionally homogeneous and extraordinary high-molecular-weight PPVs. The characterization of these materials was carried out using nuclear magnetic resonance spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 33 publications
(77 reference statements)
0
11
0
Order By: Relevance
“…Conjugated polymers are still extensively studied in fields of organic light emitting diodes, solar cell, and sensor . Planar conjugated polymers such as ladder poly( p ‐phenylene)‐type polymers (LPPP) and graphite ribbon are special members of conjugated polymer family .…”
Section: Homo and Lumo Energies And Band Gap Data Of Polymers P1 P2mentioning
confidence: 99%
“…Conjugated polymers are still extensively studied in fields of organic light emitting diodes, solar cell, and sensor . Planar conjugated polymers such as ladder poly( p ‐phenylene)‐type polymers (LPPP) and graphite ribbon are special members of conjugated polymer family .…”
Section: Homo and Lumo Energies And Band Gap Data Of Polymers P1 P2mentioning
confidence: 99%
“…The resulting solution was stirred at 50°C for 48 h. The product was extracted with dichloromethane followed by washing with brine. The solvent was dried over anhydrous MgSO 4 and removed by rotavapor. The crude product was purified by column chromatography on Al 2 O 3 using dichloromethane as eluent to yield white solid (1.3 g, 89 %).…”
Section: Synthesismentioning
confidence: 99%
“…After the discovery of electroluminescence in a polymeric semiconductor, a large effort has been made to synthesize polymers with different chromophoric moieties which make OLED-based technology a possible alternative to liquid crystal-based displays. Lately, considerable progress has been documented in several papers to develop OLED displays for other niche lighting applications [4,5]. Red, green, * E-mail: duryosahu@gmail.com and blue emitters are the prime requirements for the fabrication of full-color displays.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, the biggest challenge in the development of OLEDs is reduction of the manufacturing cost. Compared with vacuum-deposition, solution-process techniques are more suitable for low cost and large area fabrication. , However, the efficiencies of solution-processed OLEDs are generally low, especially for fluorescence devices. Recently, many efforts have been devoted to develop thermally activated delayed fluorescent (TADF) materials, which can achieve 100% internal quantum efficiency (IQE) through reverse intersystem crossing (RISC) from triplet state (T 1 ) to singlet state (S 1 ). Some important studies of TADF OLEDs fabricated by solution processing technique have been reported and the device efficiencies of them can even comparable to their vacuum-deposited counterparts. , Unfortunately, although the emission layers (EML) of these devices are fabricated by spin-coating, the electron transporting layers (ETL) are still deposited by vacuum evaporation, which inevitably increases the manufacturing cost and complexity.…”
Section: Introductionmentioning
confidence: 99%